Christology of the Old Testament ; v. 1 and a commentary on the Messianic predictions - Hengstenberg, Ernst Wilhelm, 1802-1869 (Edinburgh, Scotland T. and T. Calrk, 1858)
Contents : v. 1 : The Messianic prophecies in the Pentateuch - The Angel of the Lord in the Pentateuch and the book of Joshua - The promise in 2 Sam. vii - Messianic Psalms - 2 Sam. xxiii. 1-7 - The Song of Solomon - Messianic predictions in the prophets : The prophet Hosea - The prophet Joel - The prophet Amos - The prophecy of Obadiah - The prophet Jonah - The prophet Micah - History of interpretation.
Keywords: Christology; Bible. O.T. -- Messianic prophecies